Teachers' sense of competence in terms of ICT use: the case of secondary school teachers - El Mustapha Baytar; Hayat Elyacoubi; Nadia Saqri; Lynda Ouchaouka (Association for Learning Technology, 2023)
In the current digital age, the integration of information and communication technologies (ICT) into teaching practices has become a determining factor in learning quality. The teachers' digital competence issue has come back to the forefront because of the schools' closure due to the COVID-19 pandemic. Our study aims to assess the sense of competence in terms of ICT use of a sample of 260 secondary school teachers in the Directorate of Education in Rhamna, Morocco, by adopting a quantitative methodology. Our findings suggested that only 26.1% of the individuals in our sample reported they feel effectively competent. The pandemic made a significant change in teachers' perceptions of the importance of ICT integration and training in the field. Moreover, a cross-analysis highlighted significant relationships between the sense of competence in terms of ICT use and six independent variables: continuous training, learning readiness, gender, age, teaching experience, and school subject. Our findings would be helpful for policymakers to guide educational policies by focusing on ICT continuous training to enhance teachers' digital competence.